Dispute resolution and crises/incident management - Garcia, Mario A. (Quezon City : Wisemans Books Trading, 2021)
"It is the intention of this textbook to develop learner's acquisition of holistic and broad knowledge crisis and manners and approaches in resolving these crises."
Includes bibliographical references.
English text.
Keywords: Incident management